Constructing Patient Trust in Hospital Administrative Services: A Symbolic Interactionist Perspective on Staff-Patient Communication - Namira Azzahra (LifeSciFi, 2026)
Patient trust constitutes a foundational element in the delivery and outcomes of healthcare services, influencing how individuals engage with providers, adhere to treatments, and sustain long-term relationships with health systems. This study aims to examine the multidimensional nature of patient trust by focusing on four interconnected themes: interaction quality and symbolic communication, communicative trust mechanisms, organizational and administrative factors, and continuity of care. This study employs a qualitative descriptive design to examine the multidimensional nature of patient trust by synthesizing evidence from eleven peer-reviewed studies. Findings reveal that trust is not a static condition but rather an emergent, relational process shaped by verbal and non-verbal exchanges, biomedical rituals, institutional responsiveness, and interprofessional coordination. Healthcare providers’ communicative competence, empathy, and consistency of presence were identified as primary trust enablers, whereas fragmented care pathways, poor information exchange, and administrative inefficiencies were recurring barriers. The study contributes theoretically by applying symbolic interactionism and communicative action to explain how meaning is co-constructed in therapeutic encounters. It also highlights the need for trust-oriented communication training, patient-centered administrative redesign, and digitally supported care coordination, while enriching the literature on relational healthcare quality by bridging interpersonal dynamics and systemic factors through a holistic thematic synthesis.